THE RATE of FORCE DEVELOPMENT OBTAINED AT EARLY CONTRACTION PHASE IS NOT INFLUENCED BY ACTIVE STATIC STRETCHING - Morais de Oliveira, Andre L. [UNESP]; Greco, Camila Coelho [UNESP]; Molina, Renato [UNESP]; Denadai, Benedito S. [UNESP] (Lippincott Williams & Wilkins, 2012)
Morais de Oliveira, AL, Coelho Greco, C, Molina, R, and Denadai, BS. The rate of force development obtained at early contraction phase is not influenced by active static stretching. J Strength Cond Res 26(8): 2174-2179, 2012-The objective of this study was to investigate the influence of active static stretching on the maximal isometric muscle strength (maximal voluntary contraction [MVC]) and rate of force development (RFD) determined within time intervals of 30, 50, 100, and 200 milliseconds relative to the onset of muscle contraction. Fifteen men (aged 21.3 +/- 2.4 years) were submitted on different days to the following tests: (a) familiarization session to the isokinetic dynamometer; (b) 2 maximal isometric contractions for knee extensors in the isokinetic dynamometer to determine MVC and RFD (control); and (c) 2 active static stretching exercises for the dominant leg extensors (10 x 30 seconds for each exercise with a 20-second rest interval between bouts). After stretching, the isokinetic test was repeated (poststretching). Conditions 2 and 3 were performed in random order. The RFD was considered as the mean slope of the moment-time curve at time intervals of 0-30, 0-50, 0-100; 0-150; and 0200 milliseconds relative to the onset of muscle contraction. The MVC was reduced after stretching (285 +/- 59 vs. 271 +/- 56 N.m, p < 0.01). The RFD at intervals of 0-30, 0-50, and 0-100 milliseconds was unchanged after stretching (p > 0.05). However, the RFD measured at intervals of 0-150 and 0-200 milliseconds was significantly lower after stretching (p < 0.01). It can be concluded that explosive muscular actions of a very short duration (<100 milliseconds) seem less affected by active static stretching when compared with actions using maximal muscle strength.
Keywords: muscular torque; isometric contraction; isokinetics